MORPHOMETRIC CHARACTERISTICS OF THE ILEUM IN NEONATAL SEPSIS - Isroilov, I.; Khaitov, A.O. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To study the morphological changes and morphometric parameters of the mucous membrane of the ileum with the development of a systemic vascular inflammatory response in the form of sepsis in newborns who died in the neonatal period. Material and Methods: Autopsy material of 36 newborns who died in the neonatal period from sepsis. Including 7 with intrauterine infection and the development of sepsis, 29 - with early neonatal sepsis. For the morphological study, the ileum was completely isolated, and from three sections – proximal, middle, and distal – slices were cut out, which were fixed in 10% solution of neutral formalin for 48 h. Results: Children with various forms of sepsis in the epithelial component of the mucous membrane develop dystrophic and hyperplastic changes, ending with dysregenerative reorganizations, and alterative, disorganization and inflammatory changes occur in the stroma vascular structures, which end with the formation of lymphoid infiltration and development of sclerosis. Conclusions: The identified hyperplastic changes in the mucous membrane of the ileum are accompanied by an increase in the number of enterocytes and goblet cells in one longitudinal section of the villus.